The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1093/schbul/sbp090
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia Patients Show Deficits in Shifts of Attention to Different Levels of Global-Local Stimuli: Evidence for Magnocellular Dysfunction

Abstract: Abnormalities of attention and visual perception are well documented in schizophrenia. The global-local task is a measure of attention and perceptual organization that utilizes visual stimuli comprised of large letters (global level) made up of smaller letters (local level). Subjects identify target letters appearing at either the global or local level of the stimulus. In this study, we used a version of the global-local task specifically designed to examine lateralized hemispheric processing and attention shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 73 publications
3
25
0
Order By: Relevance
“…Also, the MD increase in the occipital lobe from HC to SZD first and SZND at the extreme end, could be related to the well-known visual processing abnormalities representing a common pathophysiological feature of the schizophrenia population as a whole (Onitsuka et al, 2007;Coleman et al, 2009;Kantrowitz et al, 2009). Particularly, the anatomical localization of the impairment can be linked to the volumetric decrease in the visual association area (Brodmann area 19) previously described in schizophrenia patients as a neuroanatomical substrate of early visual processing alterations peculiar to the disorder (Onitsuka et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the MD increase in the occipital lobe from HC to SZD first and SZND at the extreme end, could be related to the well-known visual processing abnormalities representing a common pathophysiological feature of the schizophrenia population as a whole (Onitsuka et al, 2007;Coleman et al, 2009;Kantrowitz et al, 2009). Particularly, the anatomical localization of the impairment can be linked to the volumetric decrease in the visual association area (Brodmann area 19) previously described in schizophrenia patients as a neuroanatomical substrate of early visual processing alterations peculiar to the disorder (Onitsuka et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies done by other laboratories have suggested deficits in early visual processing as well (Schwartz et al 1987; Slaghius 1998; Butler et al 2001; Green et al 2003; Coleman et al 2009; also see Slaghuis et al 2007a). …”
Section: Pathophysiology Of Etdmentioning
confidence: 99%
“…Selective impairment in shifting attention, which reflects an underlying impairment of lateralized visual information processing in the predominant hemisphere, has also been reported in patients with schizophrenia (Goleman, Gestnick, Krastoshevsky, Krause, Huang, Mendell, et al, 2009). Patients with schizophrenia made a greater number of right-side omissions in the cancellation test.…”
Section: Discussionmentioning
confidence: 90%